The dynamics of Paiku Co lake area in response to climate change. Issue 7 (6th June 2022) - Yang, Zhichong; Dai, Xiaoai; Wang, Zekun; Gao, Xiaojie; Qu, Ge; Li, Weile; Li, Jingzhong; Lu, Heng; Wang, Youlin
Abstract: With the drastic change in global climate, the wide distribution of natural lakes over the Qinghai-Tibet Plateau (TP) has attracted extensive attention due to their high climate sensitivity. In this paper, we investigated the dynamics of Paiku Co, the largest inland lake in the Qomolangma Natural Reserve, with the associated response to climate change in the past three decades. The methods used contain the water index method, the spatial and temporal fusion model, the statistical mono-window algorithm, and multi-variable linear regression. Lake area fluctuated greatly in 1990–2000, followed by a continuous shrinkage in 2000–2010, and it stabilized after that (2010–2020). We forecasted that Paiku Co would enter a slow expansion period. Conjoint analysis with climate factors showed that the area variation of Paiku Co was not significantly related to precipitation change, but negatively related to the change of air temperature and lake temperature. We found that the lake change was not dominated by a single factor but showed different climate sensitivity in each period. Especially, there was a common inflection point around 2013 that might herald the occurrence of a new trend of climate change. This article provides new ideas and solutions for the research of lakes in the Qinghai-Tibet Plateau and offers a reference for water resource management. HIGHLIGHTS: The lake area has experienced a process of sharp shrink – recovery – continuous retreat – stabilization. Paiku Co is mainly affected by temperature and exhibits variable climate sensitivity. The area of Paiku Co stabilized in 2013 and may have a slow upward trend in the future. Graphical Abstract